Building capacity to trade : a road map for development partners - Lecomte, Henri Bernard Solignac (European Centre for Development Policy Management MaastrichtNL, 2001)
Aims to provide a road map for trade capacity development and the trade policy process, as well as some practical lessons of experience with trade capacity development.